2013
DOI: 10.3810/pgm.2013.07.2676
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dyslipidemia in Patients With Chronic Kidney Disease

Abstract: The presence of dyslipidemia is associated with chronic kidney disease (CKD) in patients and likely contributes to the development of both renal disease and cardiovascular disease (CVD). In vitro and animal studies have demonstrated that renal lipid accumulation is nephrotoxic and can play a role in the initiation and/or progression of renal disease. Data from clinical studies have suggested that dyslipidemia is not causative of renal disease but likely contributes to the progression and severity of renal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…These changes could be observed in the early stages of kidney disease [25,26], and serious kidney dysfunction led to the development of severe dyslipidemia [2,3,27]. In our study, we found a higher LDL-C level in the decreased eGFR group compared to the normal eGFR group.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These changes could be observed in the early stages of kidney disease [25,26], and serious kidney dysfunction led to the development of severe dyslipidemia [2,3,27]. In our study, we found a higher LDL-C level in the decreased eGFR group compared to the normal eGFR group.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have indicated that patients with kidney disease also exhibit significant alterations in lipid metabolism and that the progression of kidney disease may lead to severe dyslipidemia [2][3][4]. Importantly, it is worth noting that disorders in lipid metabolism can also be observed in patients even in the early stage of kidney dysfunction [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of dyslipidemia is associated with CKD in patients and likely contributes to the development of both renal disease and CHD [20]. Lipoprotein metabolism is a dynamic system that can be disturbed in CKD owing to alterations in apolipoproteins, lipid transfer proteins, lipolytic enzymes and lipoprotein receptors.…”
Section: Lipid Profile Testsmentioning
confidence: 99%
“…Lipid metabolism abnormalities with alterations in lipid profiles are commonly seen in CKD patients; therefore, the prevalence of dyslipidemia in CKD is much higher than that in the general population [55,56]. Markedly reduced high-density lipoprotein quantity and function is the key dyslipidemia leading to persistent chronic inflammation, increased oxidative stress, and subsequent progression of cardiovascular disease in CKD.…”
Section: Vitamin D and Lipid Metabolismmentioning
confidence: 99%